Mapa de danos das fachadas do Teatro de Santa Isabel, Recife - Pernambuco - Macedo, Aureliano Amaro Ribeiro Souza de (2017)
This work has as its theme "The Damage Map of the Facades of the Santa Izabel Theatre". It results from a qualitative literature review, in books and websites containing scientific articles and relevant legislation, and a field visit to the historic building. It provides an overview of the selected theme including historical monuments, relevant legislation, the outer cladding system, pathological manifestations and a damage map. Moreover, it evaluates the pathologies in the building’s facades, specifying the active degradation processes, that is, the main pathologies in coatings and those associated with the building’s natural environment. The mapping of the existing conditions, including degradation and changeability of the stone material along the years, were performed, making it possible to intervene in the Historic Monument, trying to identify the causes and effects of the damage, and to produce the full report of its pathological manifestations and forms of work to satisfactorily remedy the existing damage in the historic building.